2015
DOI: 10.1162/artl_a_00184
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Candidate Relevant Subsets of Variables in Complex Systems

Abstract: In this paper we describe a method to identify "relevant subsets" of variables, useful to understand the organization of a dynamical system. The variables belonging to a relevant subset should have a strong integration with the other variables of the same relevant subset, and a much weaker interaction with the other system variables. On this basis, extending previous works on neural networks, an information-theoretic measure is introduced, i.e. the Dynamical Cluster Index, in order to identify good candidate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…It has been shown that information-theoretic measures make it possible to detect dynamical structures in complex systems [90,26,89]. The method is based on a measure called the dynamical cluster index and can detect subsets of variables that are tightly integrated among themselves and loosely interacting with the rest of the systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that information-theoretic measures make it possible to detect dynamical structures in complex systems [90,26,89]. The method is based on a measure called the dynamical cluster index and can detect subsets of variables that are tightly integrated among themselves and loosely interacting with the rest of the systems.…”
Section: Discussionmentioning
confidence: 99%
“…These subsets are possible candidates as higher-level entities for describing the organization of a system; they will be called relevant subsets (RSs, omitting the specification that they are initially just candidates). A quantitative measure, well suited for identifying them, is defined as follows (the presentation below follows the one given in [5]).…”
Section: Methodsmentioning
confidence: 99%
“…In previous works [4,5], we have introduced the Relevance Index (RI), a measure based on information theory that seems suitable for exploring the organization of complex systems. The RI makes it possible to identify, as components of a system, relevant sets of variables that show an integrated behaviour and interact more weakly with the rest of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Since these subsets are possible candidates as higher-level entities, to be used to describe the system organization, they will be called relevant subsets (omitting the specification that they are candidates). A quantitative measure, well suited for identifying them, is defined as follows (the presentation below follows the one given in [9]). …”
Section: The Relevance Indexmentioning
confidence: 99%
“…However, entropies scale with system size, so this requires considerable ingenuity. Following the original work of Tononi, an "RI method" has been developed for this purpose, where the variable is first normalized with respect to a reference case, and a statistical index is computed that allows meaningful comparisons of sets of different sizes [6,9,10]. However, quite often, these sets overlap, so the actual organization of the system remains opaque; for example, a variable may belong to a set of three variables and also to one of its four-element supersets, both endowed with fairly high values of the statistical index.…”
Section: The Relevance Indexmentioning
confidence: 99%